Adult recall of childhood female genital cutting and perceptions of its effects: A pilot study for service improvement and research feasibility. (April 2013) - Liao, L.-M.; Elliott, C.; Ahmed, F.; Creighton, S. M.
<x xml:space="preserve">Abstract</x> This study aimed to gather information from service users of an African Women's Clinic for the purposes of planning service improvement and estimating research feasibility. The report is based on 17 interviews with Somali speaking women who had experienced female genital cutting in childhood. With language barriers removed, a high percentage of clinic attendees responded positively to the invitation to participate in research. They willingly discussed their experiences of FGM and expressed their negative viewpoints about the practice of FGM, suggesting that psychosocial and psychosexual research may be feasibly carried out in specialist contexts. The results also point to the need for psychological and educational input for service improvement.